Neural responses to emotional displays by politicians: differential mu and alpha suppression patterns in response to in-party and out-party leaders - Maaike D. Homan; Mohammad Hamdan; Karlijn Hendriks; Diamantis Petropoulos Petalas (Scientific Reports)
Abstract The high levels of polarization raise concerns about individuals’ decreased ability to empathize and understand the representatives of political out-groups. As such, our political biases may lead us to misunderstand out-group politicians. In the current study, we examine the mu rhythm, a neural oscillation in the sensorimotor cortex related to the processing and understanding of other people’s actions, intentions and emotions. The mu rhythm is particularly responsive towards the emotional expressions of others and sensitive to social biases. Hence, we examine (1) whether the emotions displayed by politicians lead to more mu event-related-desynchronization (mu-ERD), (2) whether it matters which emotion (angry, happy, neutral) is displayed, and (3) whether neural responses differ when emotions are displayed by politicians we support (in-party politician) compared to politicians we do not support (out-party politician). To test this, we recorded electroencephalogram (EEG) responses during a preregistered Go/No Go mimicry experiment (N = 47, Obs = 1104), in which participants are presented with dynamic morphed emotional displays of Dutch politicians (in- and out-party) and non-politicians. We find that politicians emotional displays increase participants’ mu-ERD compared to static neutral displays. Most mu-ERD is found for out-party politicians, especially when angry. In addition, we explored alpha oscillations (related to visual attention), where we find the strongest alpha-ERD for the out-party happy condition. Overall our results suggest that our brain is specifically attuned to process the emotions of out-party politicians.